Integrative transcriptomic and proteomics profiling analyses reveals PLK1 as a target of curcumol in hepatocellular carcinoma cells - Juan Wang; Zhangchi Liu; Xiaojuan Li; Linjun Li; Tong Dou; Junfei Jin (Journal of Functional Foods, 2023)
Curcumol is a natural drug isolated from Chinese medicinal plant Rhizoma Curcumae. Though many studies have revealed its anti-tumor mechanism, there are still few studies reveal its comprehensive anti-cancer effect used multi-omics method. In this study, we aim to comprehensively analyze its anti-cancer mechanism and find its potential target in human hepatocellular carcinoma cells (HCC). In total, 1330 differential genes and 1381 differential proteins were significantly altered by curcumol in HCC. Transcriptomics and proteomics combined analysis revealed that 47 downregulated of the 97 common molecules regulated by curcumol were mainly enriched in the cell cycle pathway, including Cell Division Cycle Associated 2 (CDCA2), CDCA3, CDCA8, CDC25C, S-phase kinase-associated protein 2 (SKP2) and Polo-like kinase 1(PLK1). Furthermore, silenced PLK1 inhibited the cell growth and reversed curcumol’s effect on HCC. This paper provided a comprehensive understanding of the effect of curcumol and identified PLK1 was its potential target in HCC cells.